Assessment of reprograming capability of human fibroblast into hepatocyte-like cell by overexpression HNF4α gene in Tet-on system - Van Hanh, Nguyen; Trung Kien, Do; Cong Su, Trinh; Hai Minh, Le Thi; Thu Huong, Ngo Thi; Huong Giang, Tran Thi (Vietnam Journal of Biotechnology, 2021)
This study investigated the ability to reprogramming human fibroblast cells into hepatocyte-like cells by overexpressing HNF4a gene. The fibroblast cells isolated and primary cultured from foreskin donated by healthy patients. The HNF4a gene overexpressed through Doxycilin activatedthe vectors Tet-on-eGFP-HNF4a. The cells after the reprogramming process were evaluated by observing morphological changes, immunofluorescence staining to assess the expression of proteins specific to hepatocytes such as albumin, α-fetoprotein (AFP), HNF4a, and PAS staining to evaluate the ability to glycogen store in cells. The research has isolated and successfully primary cultured fibroblasts. The results showed that after gene transfer, the vector Tet-on-eGFP-HNF4a expressed in all cells and it did not affect the growth rate of the cell. After two weeks, the cells acquired hepatocytes morphology, and they were positive for albumin, AFP, HNF4a and PAS staining. The research has created the cells with some characteristics of liver cells from fibroblasts, however, further studies are needed to comprehensively evaluate them.